2017
DOI: 10.1590/1413-81232017228.29412016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência do consumo de medicamentos em adultos brasileiros: uma revisão sistemática

Abstract: Resumo O uso de medicamentos em adultos foi avaliado por alguns estudos de base populacional no Brasil, mas não há estimativa geral da prevalência desse consumo disponível. Nosso objetivo foi estimar a prevalência do uso de medicamentos avaliada em estudos transversais entre adultos brasileiros. Realizou-se uma revisão sistemática da literatura por meio de busca no Medline, Embase, Scopus, Lilacs, SciELO, banco de teses da Capes até janeiro de 2017. Duas revisoras selecionaram as pesquisas, extraíram os dados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
1
11
0
6
Order By: Relevance
“…The prevalence of medicine consumption found in our study was similar to the one reported in a systematic review conducted in Brazil, about 50% ( Gomes et al., 2017 ). Our study found an increased lack of access to treatments when compared to a population-based study conducted in Porto Alegre, Southern Brazil with 2,988 individuals in 2003, which found that 5% of the participants who used medicines in the 15 days prior to the interview could not obtain appropriate treatment ( Bertoldi et al., 2009 ).…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of medicine consumption found in our study was similar to the one reported in a systematic review conducted in Brazil, about 50% ( Gomes et al., 2017 ). Our study found an increased lack of access to treatments when compared to a population-based study conducted in Porto Alegre, Southern Brazil with 2,988 individuals in 2003, which found that 5% of the participants who used medicines in the 15 days prior to the interview could not obtain appropriate treatment ( Bertoldi et al., 2009 ).…”
Section: Discussionsupporting
confidence: 90%
“…The presence of disease usually requires pharmacological management, which is effective both for preventing and treating health disorders, reducing or eliminating the symptoms of disease. The majority of epidemiological information available describes the prevalence and factors associated with medication use for the general adult population [13][14][15][16] . However, although there are many studies assessing health risks among elementary teachers [6][7][8][9][10] , no studies have described the medication use profile in this population.…”
Section: Introductionmentioning
confidence: 99%
“…There are still relatively few reviews in the field of PS, be they systematic, narrative, scoping, or qualitative. This may be because the growth in research in this area is only recent and there is therefore an unmet need to bring together enough references on the same topic to ensure a robust review [40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%